(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
This long conversation with Marvin Carlson took place in March 2012 at CUNY (City University of New York), where Carlson is professor of Theater, Comparative Literature and Middle-East Studies. His deep knowledge of the topic “performance” makes him one of the most authoritative voices in the field; yet, at the same time, the fact that he is not a Performance Studies professor, allows him to be a conscious and informed “alternative voice”. In this way he can provide a different perspective from another angle, but still deeply aware and expert in the subject matter. The first substantial part of the conversation focuses on issues concerning the ontological definition of “performance”, while the second part is dedicated to the analysis of Performance Studies, of the contributions that this new discipline has generated in the field of Theatre Studies, and of its possible interdisciplinary or postdisciplinary connotation, here challenged by Carlson. Thirdly, the attention focuses on the intertwining of theory and practice in the field of Performance Studies, an intersection that was coveted and sought in the early eighties, but that never quite materialized according to Marvin Carlson. Furthermore, regarding the possible lack of importance given to the historiographical component among performance scholars, Carlson considers it as a quite common matter within Performance Studies.